PENGARUH MEDIA ULAR TANGGA BERHITUNG TERHADAP PENINGKATAN KEMAMPUAN OPERASI HITUNG BILANGAN BULAT SISWA SD - SETIAWAN, Muhammad Agung Surya (2014)
This research is motivated by the lack of application and use of instructional media in the teaching of mathematics, and therefore become less active students in the learning process so that students' ability to perform arithmetic operations become less good and not in line with expectations. This research was conducted in the District of SD Negeri 1 ManggungjayaRajapolahTasikmalaya regency. The purpose of this study was to determine the ability of students to perform arithmetic operations of addition and subtraction of integers before using Snakes and Ladders Numeracy media and to know the results of the use of media Snakes and Ladders Numeracy to increased students' ability to perform arithmetic operations addition and subtraction of integers. The method used is pre-experiment with populations Elementary School fourth grade students in District 1 ManggungjayaRajapolahTasikmalayasiswa.Instrumen totaling 51 people who used that pretest and posttest on the material arithmetic operations of addition and subtraction of integers. The results showed that the average arithmetic operation capability of addition and subtraction of integers students seen from the results of the pretest score of 66.02 (low), the average ability of arithmetic operations of addition and subtraction of integers students seen from the results of the posttest scores of 152.39 (very high), and the use of snakes and ladders Numeracy media can affect the ability of arithmetic operations of addition and subtraction of integers students. This is evidenced by the results of the t-test scores significance (Sig.) of 0.000. Keyword : Snake Ladder Counting media, the ability of addition and reduction operation of integer